Efficacy of Self Hypnosis for Reducing Autonomic Symptoms in High School Students with Social Anxiety Disorder - One, Syahrun El Mubaraq; Salsabila, Dewi Syahrany; Fatima, Nur; Morundu, Deysin; Kesumasari, Ni Made; Yusuf, Jalaluddin (Universitas Muhammadiyah Surakarta, 2024)
Background: Social anxiety disorder (SAD) disrupts adolescents' social and academic functioning, often causing autonomic symptoms like increased heart rate, elevated blood pressure, and rapid breathing. Hypnotherapy, specifically using future pacing, may help reduce these symptoms, yet its impact in adolescents with SAD is underexplored. Aim: This study aims to evaluate the effectiveness of hypnotherapy on autonomic symptoms in high school students in Poso with social phobia using future pacing techniques. Method: Pretest-posttest experimental design was conducted with 36 students diagnosed with SAD. Participants were split into a treatment group, receiving six hypnotherapy sessions over three weeks, and a control group without intervention. Blood pressure, pulse, and respiratory rate were measured before and after a public speaking task to assess autonomic response changes. Results: The treatment group showed significantly reduced autonomic symptoms compared to the control group, with meaningful reductions in blood pressure, pulse, and respiratory rate (p < 0.05), supporting the intervention’s effctiveness. Conclusion: Hypnotherapy utilizing future pacing is effective in reducing autonomic symptoms associated with social phobia in high school students, supporting its application as a self-therapy method to alleviate social anxiety symptoms.